2009
DOI: 10.1128/jvi.01318-09
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylases 1 and 2 Are Phosphorylated at Novel Sites during Varicella-Zoster Virus Infection

Abstract: ORF66p, a virion-associated varicella-zoster virus (VZV) protein, is a member of a conserved Alphaherpesvirinae kinase family with homology to herpes simplex virus U S 3 kinase. Expression of ORF66p in cells infected with VZV or an adenovirus expressing only ORF66p results in hyperphosphorylation of histone deacetylase 1 (HDAC1) and HDAC2. Mapping studies reveal that phosphorylation is at a unique conserved Ser residue in the C terminus of both HDACs. This modification requires an active kinase domain in ORF66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
61
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 56 publications
(113 reference statements)
5
61
0
Order By: Relevance
“…In addition, autonomous expression of HSV-1 US3 and US3.5 resulted in enhanced expression of viral or cellular genes, similar to what occurs in cells treated with sodium butyrate, a pan-tropic HDAC inhibitor (43,45). Treatment of cells with sodium butyrate also partially complements the growth defect associated with a VZV mutant lacking ORF66p kinase activity (61). These studies suggest a mechanism whereby US3 kinasemediated hyperphosphorylation of HDAC1 and HDAC2 inhibits their repressive activity to allow efficient gene expression and viral replication.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…In addition, autonomous expression of HSV-1 US3 and US3.5 resulted in enhanced expression of viral or cellular genes, similar to what occurs in cells treated with sodium butyrate, a pan-tropic HDAC inhibitor (43,45). Treatment of cells with sodium butyrate also partially complements the growth defect associated with a VZV mutant lacking ORF66p kinase activity (61). These studies suggest a mechanism whereby US3 kinasemediated hyperphosphorylation of HDAC1 and HDAC2 inhibits their repressive activity to allow efficient gene expression and viral replication.…”
mentioning
confidence: 59%
“…Phosphorylation of HDACs is the most extensively studied modification, and reports have shown that enzy-matic activity, cellular localization, and protein-protein interactions of HDACs are regulated in this manner (reviewed in reference 18). HDAC1 and HDAC2 are hyperphosphorylated during HSV-1, HSV-2, and VZV infection in a US3 kinasedependent manner (26,39,43,61). In addition, autonomous expression of HSV-1 US3 and US3.5 resulted in enhanced expression of viral or cellular genes, similar to what occurs in cells treated with sodium butyrate, a pan-tropic HDAC inhibitor (43,45).…”
mentioning
confidence: 86%
“…This is in contrast to findings for HSV-1 and VZV and indicates virus-specific US3-independent mechanisms of HDAC hyperphosphorylation. Inhibition of HDAC activity increased plaquing efficiency of US3-null virus for PRV and VZV, but not for HSV-1, pointing to virus-and celldependent differences in the functional significance of US3-mediated HDAC modification (223,224). …”
Section: Herpesvirusesmentioning
confidence: 94%
“…Over the last couple of years, it has become evident that US3 also affects gene expression. US3 orthologs of HSV-1, HSV-2, PRV, and VZV phosphorylate HDAC1 and -2, thereby inhibiting the deacetylation of histones, which otherwise silence gene expression (151,176,223,224). US3-mediated phosphorylation of HDAC2 occurs at a C-terminally located conserved serine residue (224).…”
Section: Herpesvirusesmentioning
confidence: 99%
See 1 more Smart Citation